XANES measurements of the rate of radiation damage to selenomethionine side chains - Holton, James M (Journal of synchrotron radiation, 2007)
The radiation-induced disordering of selenomethionine (SeMet) side chains represents a significant impediment to protein structure solution. Not only does the increased B-factor of these sites result in a serious drop in phasing power, but some sites decay much faster than others in the same unit cell. These radio-labile SeMet side chains decay faster than high-order diffraction spots with dose, making it difficult to detect this kind of damage by inspection of the diffraction pattern. The selenium X-ray absorbance near-edge spectrum (XANES) from samples containing SeMet was found to change significantly after application of X-ray doses of 10-100 MGy. Most notably, the sharp ;white line' feature near the canonical Se edge disappears. The change was attributed to breakage of the Cgamma-Se bond in SeMet. This spectral change was used as a probe to measure the decay rate of SeMet with X-ray dose in cryo-cooled samples. Two protein crystal types and 15 solutions containing free SeMet amino acid were examined. The damage rate was influenced by the chemical and physical condition of the sample, and the half-decaying dose for the selenium XANES signal ranged from 5 to 43 MGy. These decay rates were 34- to 3.8-fold higher than the rate at which the Se atoms interacted directly with X-ray photons, so the damage mechanism must be a secondary effect. Samples that cooled to a more crystalline state generally decayed faster than samples that cooled to an amorphous solid. The single exception was a protein crystal where a nanocrystalline cryoprotectant had a protective effect. Lowering the pH, especially with ascorbic or nitric acids, had a protective effect, and SeMet lifetime increased monotonically with decreasing sample temperature (down to 93 K). The SeMet lifetime in one protein crystal was the same as that of the free amino acid, and the longest SeMet lifetime measured was found in the other protein crystal type. This protection was found to arise from the folded structure of the protein molecule. A mechanism to explain observed decay rates involving the damaging species following the electric field lines around protein molecules is proposed